Integrating corpus-based tools in translators' work environment: cognitive and professional implications - Peraldi, Sandrine (Revista Internacional de Organizaciones, 2019)
Despite the growing recognition of corpora-induced benefits for translation quality, the use of corpus technology remains an exception in a professional setting. This article describes the results of a pilot study aimed at integrating corpus-based tools into the work environment of legal/financial translators. In particular, the paper examines resistance and success factors with a view to encouraging the progressive integration of corpus technology into translators' toolboxes.